2016 Project Elijah Final Report - Furey, Joshua; Maraccini, Jared; Phakousonh, Cheyenne; Rasmussen, Justin; Schotte, Jonathan (Proceedings of the Wisconsin Space Conference, 2017)
We are the 2016 Project Elijah Payload team, and we were excited to work on the payload and perform some cool experiments. This report goes in detail about the payload design, vegetation health monitoring system, immersive experience, stabilization system, and the air quality system.